2006
DOI: 10.1117/1.2192787
|View full text |Cite
|
Sign up to set email alerts
|

Automated three-axis gonioreflectometer for computer graphics applications

Abstract: We describe an automated three-axis BRDF measurement instrument that can help increase the physical realism of computer graphics images by providing light scattering data for the surfaces within a synthetic scene that is to be rendered. To our knowledge, the instrument is unique in combining wide angular coverage (beyond 85° from the surface normal), dense sampling of the visible wavelength spectrum (1024 samples), and rapid operation (less than ten hours for complete measurement of an isotropic sample). The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…Li, et al 7) have proposed a three-axis instrument. However, because the angle needs to be altered mechanically, the measurement of dense BRDFs takes a long time.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Li, et al 7) have proposed a three-axis instrument. However, because the angle needs to be altered mechanically, the measurement of dense BRDFs takes a long time.…”
Section: Related Workmentioning
confidence: 99%
“…This means that it is impractical to measure dense BRDFs using a gonioreflectometer. In fact, Li, et al 7) reported that the real measuring time becomes about 9-10 hours even if the number of angular configurations is 10…”
Section: Problems Of Brdf Measurementmentioning
confidence: 99%
“…The challenges lie within having a high angular resolution, dense sampling of the visible wavelength spectrum, and rapid operation as measurements can take hours [27]. Researchers often rely on self-built gonioreflectometers or customized optical systems.…”
Section: Gloss Measurementmentioning
confidence: 99%
“…BRDF is measured with a gonioreflectometer, which consists of light source and detector moveable in relation to the sample surface [27]. The challenges lie within having a high angular resolution, dense sampling of the visible wavelength spectrum, and rapid operation as measurements can take hours [27].…”
Section: Gloss Measurementmentioning
confidence: 99%
“…In this case, the function being measured has only three angular dimensions, so one requires only three degrees of freedom in the acquisition system. In the gonioreflectometer recently built at Cornell [LFTW06], this is accomplished by having two degrees of freedom in the orientation of the planar sample and one additional degree of freedom in the angular position of the source. Using this system, one can acquire 31 spectral samples per camera/source position (roughly 10nm increments over the visible spectrum), and capturing 1000 angular samples (which is a very sparse covering of the 3D angular domain) takes approximately 10 hours.…”
Section: The Gonioreflectometermentioning
confidence: 99%